On the Origin of Spectral Features Observed during Thermonuclear X-Ray Bursts and in the Aftermath Emission of a Long Burst from 4U 1820–30 - Gaurava K. Jaisawal; Jérôme Chenevez; Tod E. Strohmayer; Hendrik Schatz; J. J. M. in ’t Zand; Tolga Güver; Diego Altamirano; Zaven Arzoumanian; Keith C. Gendreau (The Astrophysical Journal)
We study 15 thermonuclear X-ray bursts from 4U 1820–30 observed with the Neutron Star Interior Composition Explorer (NICER). We find evidence of a narrow emission line at 1.0 keV and three absorption lines at 1.7, 3.0, and 3.75 keV, primarily around the photospheric radius expansion phase of most bursts. The 1.0 keV emission line remains constant, while the absorption features, attributed to wind-ejected species, are stable but show slight energy shifts, likely due to combined effects of Doppler and gravitational redshifts. We also examine with NICER the “aftermath” of a long X-ray burst (a candidate superburst observed by MAXI) on 2021 August 23 and 24. The aftermath emission recovers within half a day from a flux depression. During this recovery phase, we detect two emission lines at 0.7 and 1 keV, along with three absorption lines whose energies decrease to 1.57, 2.64, and 3.64 keV. Given the nature of the helium white dwarf companion, these absorption lines during the aftermath may originate from an accretion flow, but only if the accretion environment is significantly contaminated by nuclear ashes from the superburst. This provides evidence of temporary metal enhancement in the accreted material due to strong wind loss. Moreover, we suggest that the absorption features observed during the short X-ray bursts and in the superburst aftermath share a common origin in heavy nuclear ashes enriched with elements like Si, Ar, Ca, or Ti, either from the burst wind or from an accretion flow contaminated by the burst wind.